User Satisfaction To The Quality Of Repository Services At An Academic Library: Applying Libqual+ - Antasari, Indah Wijaya (IQRA`: Jurnal Perpustakaan dan Informasi, 2024)
Universitas Islam Negeri (UIN) Prof Saifuddin Zuhri's Library has a collection of theses, dissertations, and research reports from print to digital, which can be accessed through the institution's repository. Thesis and repository services are needed by final-year students who are completing thesis assignments. This paper assesses the quality of repository services using the LibQual+TM standard as set by the Association of Research Libraries (see http://libqual.org). The research method is quantitative, with the UIN student population from semester 8 and semester. The number of samples was 93 taken randomly. The results showed that the quality of repository services got an average value of 3.12 on a scale of 4.0, which indicates The lowest value of 2.76 shows that although users are satisfied as a whole, they still feel that the facilities in the institutional repository are incomplete with several proposals for improving the benefits of institutional repositories. Student suggestions for improvment include: an adequate internet network, an easy search menu, instruction of the functions of the repository and more intensive promotion of the repository to heighten access to research information.  This study contributes heightened understanding for the value of digitized repository services in academic libraries as a vital information literacy tool for college students.